2021
DOI: 10.3390/ani11123338
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fresh Citrus Pulp Supplementation on Animal Performance and Meat Quality of Feedlot Steers

Abstract: The use of fruit by-products such as citrus pulp represents a feeding ingredient that deserves to be evaluated as an energy source in animal rations. Thirty-six British breed steers were allotted to one of the three feeding treatments (12 steers/treatment): 0%, 15% and 30% of fresh citrus pulp inclusion in the ration in a randomized complete block design to evaluate animal performance and carcass and meat quality traits. In the present study, the inclusion of fresh citrus pulp up to 30% of the diet did not aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
0
11
2
Order By: Relevance
“…However, the value of protein content in the whole C. limon and C. clementina fruits was lesser in value when compared to the one (14.90%) reported by Luzardo et al (2021). Fresh citrus fruits can be used in diets for feedlot steers as it was reported to give a positive effect on animal productivity, especially as a result of a positive result on their dry matter intake and a better feed to weight gain ratio of the animal (Luzardo et al, 2021). Citrus fruit by-products have also been used to improve the performance and milk production of sheep and other ruminants (Bampidis and Robinson, 2006;Zoiopoulos et al, 2008;Bakr, 2020).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…However, the value of protein content in the whole C. limon and C. clementina fruits was lesser in value when compared to the one (14.90%) reported by Luzardo et al (2021). Fresh citrus fruits can be used in diets for feedlot steers as it was reported to give a positive effect on animal productivity, especially as a result of a positive result on their dry matter intake and a better feed to weight gain ratio of the animal (Luzardo et al, 2021). Citrus fruit by-products have also been used to improve the performance and milk production of sheep and other ruminants (Bampidis and Robinson, 2006;Zoiopoulos et al, 2008;Bakr, 2020).…”
Section: Discussioncontrasting
confidence: 60%
“…68%) of dried Citrus and orange fruit, which was reported by several other authors (Bampidis and Robinson, 2006;Allam et al, 2011Allam et al, , 2020Palangi et al, 2013;Santos et al, 2014). However, the value of protein content in the whole C. limon and C. clementina fruits was lesser in value when compared to the one (14.90%) reported by Luzardo et al (2021). Fresh citrus fruits can be used in diets for feedlot steers as it was reported to give a positive effect on animal productivity, especially as a result of a positive result on their dry matter intake and a better feed to weight gain ratio of the animal (Luzardo et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…stated that the high nutritional value of citrus by‐products makes them play a key role in livestock fattening without altering animal health. Luzardo et al ., 20 Scerra et al ., 39 and De Evan et al 40 . also confirmed that feeding by mixing up to 35% of fruit waste/byproducts with byproducts of cereal crops does not have a significant effect on the health and meat quality of ruminants, and hence suggested, as a promising method for improving feed quality, reducing the environmental impact and cost of feed without compromising animal health and meat quality.…”
Section: Introductionmentioning
confidence: 85%
“…Parallel to increasing waste generation, global energy demand also increased with an increasing rate of industrialization, urbanization, and continuous population growth 20 . According to the International Renewable Energy Agency 21 and the International Renewable Energy Agency (IRENA), 22 approximately 1 billion people worldwide are currently without energy, and demand is expected to increase by more than 50% by 2050.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation